Considerações sobre a fenomenologia hermenêutica de Heidegger - SEIBT, Cezar Luís (Universidade Federal do Pará, 2023)
The text points to what characterizes Heidegger's phenomenology, situating it in its larger context in the 1920s to 1930s. Heidegger intends a phenomenology in the phenomenological sense and this implies in his work of deconstruction of the metaphysical tradition to rediscover the meaning of being, buried by the daily tendency of human existence involved with beings (objects and their representations). The things themselves will not be, for this author, the objects or entities, but the enabling horizon of the beings, which is the sense of being. Moreover, it will be hermeneutic because it is about recognizing the finite and historical condition of the human being as an interpreter already always involved in a comprehensive circle.